Intranasal Delivery of Thermostable Subunit Vaccine for Cross-Reactive Mucosal and Systemic Antibody Responses Against SARS-CoV-2 - Nguyen, Khue G.; Mantooth, Siena M.; Vrabel, Maura R.; Zaharoff, David A. (Frontiers in Immunology, 2022)
Despite the remarkable efficacy of currently approved COVID-19 vaccines, there are several opportunities for continued vaccine development against SARS-CoV-2 and future lethal respiratory viruses. In particular, restricted vaccine access and hesitancy have limited immunization rates. In addition, current vaccines are unable to prevent breakthrough infections, leading to prolonged virus circulation. To improve access, a subunit vaccine with enhanced thermostability was designed to eliminate the need for an ultra-cold chain. The exclusion of infectious and genetic materials from this vaccine may also help reduce vaccine hesitancy. In an effort to prevent breakthrough infections, intranasal immunization to induce mucosal immunity was explored. A prototype vaccine comprised of receptor-binding domain (RBD) polypeptides formulated with additional immunoadjuvants in a chitosan (CS) solution induced high levels of RBD-specific antibodies in laboratory mice after 1 or 2 immunizations. Antibody responses were durable with high titers persisting for at least five months following subcutaneous vaccination. Serum anti-RBD antibodies contained both IgG1 and IgG2a isotypes suggesting that the vaccine induced a mixed Th1/Th2 response. RBD vaccination without CS formulation resulted in minimal anti-RBD responses. The addition of CpG oligonucleotides to the CS plus RBD vaccine formulation increased antibody titers more effectively than interleukin-12 (IL-12). Importantly, generated antibodies were cross-reactive against RBD mutants associated with SARS-CoV-2 variants of concern, including alpha, beta and delta variants, and inhibited binding of RBD to its cognate receptor angiotensin converting enzyme 2 (ACE2). With respect to stability, vaccines did not lose activity when stored at either room temperature (21-22°C) or 4°C for at least one month. When delivered intranasally, vaccines induced RBD-specific mucosal IgA antibodies, which may protect against breakthrough infections in the upper respiratory tract. Altogether, data indicate that the designed vaccine platform is versatile, adaptable and capable of overcoming key constraints of current COVID-19 vaccines.